Uptake and transport of antibiotic kasugamycin in castor bean (Ricinus communis L.) seedlings - Zhang, Hongzhen; Zhang, Chenghua; Xiang, Xiaolong; Zhang, Qilun; Zhao, Wei; Wei, Guoyu; Hu, Anlong (Frontiers in Microbiology, 2022)
Kasugamycin (KSM), an aminoglycoside antibiotic, has been widely used for the management of plant diseases, especially for the control of rice blast in Asia. However, its uptake mechanism and transport in plants are still obscure. The castor bean (Ricinus communis) seeding, a model plant for phloem transport, was used to study the mechanism of uptake and transport of KSM. Results showed that cotyledon-applied KSM could transport into the phloem and distributed in the root and shoot of the plant. The temperature, concentration, pH and energy inhibitors had significant effects on the uptake of KSM, indicating that the uptake of KSM was mediated by an active, energy-consuming carrier system. Competitive substrates (glucose, phlorizin, and D-chiro-inositol (DCI) of sugar transporter inhibited the uptake of KSM, suggesting that a kind of sugar transporter-mediated the active uptake of KSM. All the results showed that the uptake of KSM was mediated by a sugar transporter, and it could transport from shoot to root in plants via the phloem. The study preliminary elucidated the plant-microbe interactions in the context of the transport of microbial secondary metabolites in plants. It has certain significance for the scientific application of antibiotics and biological control of plant diseases and provides a theoretical basis for the development of bidirectional transport pesticides.